Short-Term Outcomes of Single-Incision Laparoscopic Surgery for Colorectal Cancer: A Single-Center, Open-Label, Non-Inferiority, Randomized Clinical Trial - Song, Zijia; Liu, Kun; Li, You; Shi, Yiqing; Jiang, Yimei; Wang, Changgang; Chen, Xianze; Zhang, Tao; Ji, Xiaopin; Zhao, Ren (Frontiers in Oncology, 2021)
Objective: To date, well designed randomized controlled trials examining the safety, efficacy and long-term outcomes of single-incision laparoscopic surgery (SILS) for colorectal cancer are scarce. The aim of current study was to compare short-term outcomes of SILS for colorectal cancer to conventional laparoscopic surgery (CLS). Methods: Between June 28, 2017, and June 29, 2019, a single-center, open label, non-inferiority, randomized clinical trial was conducted at the Department of General Surgery, Ruijin Hospital (North), Shanghai Jiaotong University School of Medicine in Shanghai, China. In total, 200 patients diagnosed or suspected of colorectal cancer (cT1-4aN0-2M0) were randomly assigned to either SILS or CLS group in a 1:1 ratio. The primary outcome was early morbidity rate. Secondary outcomes included intraoperative outcomes, pain intensity, postoperative recovery, pathologic outcomes and long-term outcomes. Results: In total, 193 participants (SILS, 97; CLS, 96) were analyzed in the modified intention-to-treat (MITT) population. Among them, 48 underwent right hemicolectomy (SILS n=23, 23.7% and MLS n=25, 26%), 15 underwent left hemicolectomy (SILS n=6, 6.2% and MLS n=9, 9.4%), 1 underwent transverse colectomy (MLS n=1, 1%), 57 underwent sigmoidectomy (SILS n=32, 33% and MLS n=25, 26%) and 72 underwent anterior resection (SILS n=36, 37.1% and MLS n=36, 37.5%). No significant differences were observed in the baseline characteristics. The intraoperative complication was comparable between the 2 groups (5 (5.2%) vs 4 (4.2%); difference, 1%; 95%CI, -5.8% to 7.8%; p>0.999) and so was postoperative complication rates (10 (10.3%) vs 14 (14.6%), difference, -4.3%; 95%CI, -13.9% to 5.3%; p=0.392). The SILS group showed shorter incision length (median (i.q.r.), 4 (3.5-5) vs 6.6 (6-7.5), p<0.001) and lower VAS scores on the first (median (i.q.r.), 4 (3-5) vs 4 (4-5), p=0.002) and the second day (median (i.q.r.), 2 (1.5-3) vs 3(2-4), p<0.001) after surgery. No statistically significant difference was found in other measured outcomes. Conclusions: Compared with CLS, SILS performed by experienced surgeons for selected colorectal cancer patients is non-inferior with good short-term safety and has the advantage of reducing postoperative pain. Trial Registration: ClinicalTrials.gov Identifier: NCT03151733